Development of Grade 10 Students’ Argumentation Skills in Immune System against COVID-19 through Online Socio-Scientific Issues (SSIs)-Based Teaching - Yokyong, Saharad; Pitiporntapin, Sasithep; Pruekpramool, Chaninan (Ratchaphruek Journal, 2022)
This classroom action research aimed to enhance students’ argumentation skills through online socio-scientific issues (SSIs)-based teaching. The study group included 40 grade 10 students in the science and mathematics program of a government secondary school in Bangkok, which were selected by purposive selection. The research instruments included the argumentation skills test and the informal interview form. The argumentation skills test included one socio-scientific issue in COVID-19 vaccination with four open-ended questions measuring four components: 1) Claim and warrant; 2) Evidence; 3) Counterargument; and 4) Supportive argument. The quantitative data were analyzed by frequencies, percentages, and gains cores and the qualitative data were analyzed by content analysis. The findings revealed that after learning with online SSIs-based teaching, all students (100.00%) improved their argumentation skills. The highest number of students was at intermediate level of argumentation skills. Evidence was the most developed component, while supportive argument was the least developed component.